High tissue expression of TLRs combined with high density of tumor infiltrating lymphocytes predicts a better prognosis in colorectal cancer patients - Beilmann-Lehtonen Ines; Kasurinen Jussi; Hagström Jaana; Kaprio Tuomas; Böckelman Camilla; Haglund Caj (Public Library of Science, 2025)
Background
Colorectal cancer causes 935,000 cancer deaths yearly. High local immune cell infiltration serves as a positive prognostic factor in CRC. Toll-like receptors (TLRs) induce innate immune responses and lead to adaptive immune system activation. TLRs play protumorigenic and antitumorigenic roles. We aimed to explore the relationship between TLR immunoexpressions and the infiltration densities of T-lymphocytes in CRC.
Methods
Immunohistochemical TLR2, TLR4, TLR5, and TLR7 positivity and the density of CD3- and CD8-positive cells in tumoral and stromal tissue were evaluated from the tissue microarray slides of 549 consecutive CRC surgical patients treated at Helsinki University Hospital, Finland, between 1998 and 2005. We calculated the associations and correlations using Pearson’s chi-square and Spearman’s correlation tests, generating survival curves using the Kaplan–Meier method.
Results
Positive intratumoral CD3 and CD8 densities associated with a high TLR2 expression (p < 0.001 and p = 0.001, respectively) and a high TLR4 expression (p = 0.013 and p = 0.025). A low TLR5 immunoexpression associated with negative intratumoral CD3 (p = 0.001) and CD8 (p = 0.011) and a low stromal CD3 (p = 0.001). No association or correlation emerged between TLR7 immunoexpression and CD3 or CD8 cell density. A low CD3–CD8 tumor–stroma index indicated a worse prognosis among all TLR subgroups, except the TLR7-negative subgroup.
Conclusions
We detected significant associations and correlations between high tissue TLR2, TLR4, and TLR5 immunoexpressions and high densities of CD3- and CD8-positive cells. Combining these markers may improve the prognostic evaluation of CRC patients.